2014
DOI: 10.4149/neo_2014_068
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 9-cis retinoic acid and all-trans retinoic acid in combination with verapamil on P-glycoprotein expression in L1210 cells

Abstract: The development of the most common multidrug resistance (MDR) phenotype is associated with a massive overexpression of P-glycoprotein (P-gp) in neoplastic cells. In the current study, we used three L1210 cell variants: S cells - parental drug-sensitive cells; R cells - drug-resistant cells with P-gp overexpression due to selection with vincristine; T cells - drug-resistant cells with P-gp overexpression due to stable transfection with the pHaMDRwt plasmid, which encodes human full-length P-gp. Several authors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 45 publications
(64 reference statements)
0
11
0
Order By: Relevance
“…We periodically control P-gp expression at the mRNA and protein levels by RT-PCR, western blotting and confocal immunocytochemistry [ 51 ].…”
Section: Methodsmentioning
confidence: 99%
“…We periodically control P-gp expression at the mRNA and protein levels by RT-PCR, western blotting and confocal immunocytochemistry [ 51 ].…”
Section: Methodsmentioning
confidence: 99%
“…These two receptors could be classified as adopted orphan receptors with a specific ligands (including VCR Breier et al 2013b) identified in recent years (Shi 2007) and are dimerization partners of retinoid X receptors (Saeki et al 2010) with known ligand 9-cis retinoic acid (Brtko and Thalhamer 2003;Brtko and Dvorak 2011). Interestingly, the role of regulatory pathway of nuclear receptors for retinoids in development of P-gp-mediated MDR could take part (Sulova et al 2008(Sulova et al , 2012Breier et al 2014). Nestin was assumed to be transcriptionally controlled by the orphan receptor Nurr1 (Kappen and Yaworsky 2003), which the ligands are currently unknown (Shi 2007).…”
Section: Mdr1→mentioning
confidence: 99%
“…9‐cisRA which binds to both retinoic acid receptors (RAR) and nuclear retinoid X receptors (RXR) prevented prostate carcinogenesis in rats, reduced growth and induced apoptosis of human prostate cancer cells in a dose‐dependent method . 9‐cisRA induced the downregulation of P‐glycoprotein, the overexpression of which develops MDR phenotype in L1210 lymphocytic leukemia cells . It also directly retarded the cell cycle in a concentration‐ and time‐dependent method in NCI‐H295R adrenocortical cancer cells as well as reduced tumor growth in the in vivo xenograft model .…”
Section: Discussionmentioning
confidence: 99%